Bibliometric Analysis of Author Collaboration in Khizanah al-Hikmah: Journal of Library, Information and Archival Science in 2018-2022 - Nurmuawiyah, Nurmuawiyah; Habsyi, Sitti Husaebah Pattah (Inkunabula: Journal of Library Science and Islamic Information, 2025)
This study presents a bibliometric analysis of author collaboration in Khizanah al-Hikmah: Jurnal Ilmu Perpustakaan, Informasi dan Kearsipan from 2018 to 2022. The objective is to determine the level of author collaboration, identify the most frequent collaborating authors, and examine which institutions are most actively involved in collaborative research published in the journal during the stated period. This research employed a quantitative approach. The sample consisted of all 98 articles published in the journal between 2018 and 2022. Data collection and processing were conducted from August to December 2023 using the Publish or Perish application. Data analysis was carried out using VOSviewer and bibliometric techniques based on Subramanyam's formula for measuring collaboration. The findings reveal a high level of author collaboration, with a collaboration index of 0.73 (73%). A total of 72 articles were produced through collaborative research, while 26 were authored individually. The author named Tupan emerged as the most collaborative contributor, having co-authored eight published articles during the study period. This indicates that Tupan has made significant contributions to the journal's scholarly development. Furthermore, Universitas Indonesia was identified as the most frequently collaborating institution, contributing eight articles (11.1%) of the 35 documented in the journal from 2018 to 2022.AbstrakTujuan penelitian ini adalah untuk mengetahui tingkat kolaborasi pengarang, mengidentifikasi pengarang yang paling sering melakukan kolaborasi, serta mengkaji lembaga-lembaga yang paling aktif terlibat dalam riset kolaboratif yang dipublikasikan dalam jurnal tersebut. Penelitian ini menggunakan pendekatan kuantitatif. Sampel penelitian terdiri atas seluruh artikel yang diterbitkan dalam kurun waktu tersebut, yaitu sebanyak 98 artikel. Pengumpulan dan pengolahan data dilakukan pada bulan Agustus hingga Desember 2023 menggunakan aplikasi Publish or Perish. Analisis data dilakukan dengan bantuan VOSviewer serta teknik bibliometrik berdasarkan rumus kolaborasi Subramanyam. Hasil penelitian menunjukkan bahwa tingkat kolaborasi pengarang tergolong tinggi, dengan indeks kolaborasi sebesar 0,73 (73%). Sebanyak 72 artikel dihasilkan melalui kolaborasi, sementara 26 artikel ditulis secara individu. Penulis bernama Tupan merupakan pengarang yang paling sering berkolaborasi, dengan total 8 artikel yang diterbitkan dalam jurnal selama periode penelitian. Hal ini menunjukkan bahwa Tupan memberikan kontribusi signifikan terhadap perkembangan keilmuan dalam jurnal tersebut. Selain itu, Universitas Indonesia teridentifikasi sebagai lembaga yang paling sering terlibat dalam kolaborasi, dengan kontribusi sebanyak 8 artikel (11,1%) dari total 35 lembaga yang tercatat melakukan kolaborasi pada jurnal ini selama tahun 2018 hingga 2022.